3 Point Shoulder Injection (3PSI) - a novel approach to shoulder pain - Sundrasegaran, Punithamalar; Suhaimi, Anwar; Singh, Lakvinder; Abu Hassan, Salmah Anim (MRE Press, 2023)
Background There is a high prevalence of chronic shoulder pain reported among healthcare workers and labourers in Malaysia. Rotator cuff disorders, acromioclavicular joint (ACJ) disease and glenohumeral joint (GHJ) disorders are the most common causes of shoulder pain. This study aims to report on the effect of ultrasound-guided 3PSI prolotherapy in patients with chronic shoulder pain. Method Thirty patients who were diagnosed with pathologies encompassing the ACJ, subacromial space and GHJ, a Pain Numerical Rating Scale (NRS) ≥ 5 and shoulder pain for at least three months were included in this study by using convenience sampling. A single 21G needle with a total of 5mls prolotherapy (2mls of Dextrose 50%, 1mls Lignocaine 1% and 1mls of water for injection) was introduced from the ACJ to the GHJ using the ultrasound guidance. Prolotherapy was introduced to GHJ, followed by subacromial space structure and finally to the ACJ as the single needle being withdrawn upwards. Results An ANOVA with repeated measures was used to compare the pain score at baseline, immediately post 3PSI, and at follow-up (at 2 weeks and 6 weeks post 3PSI) for all 30 patients. There was a statistically significant association among the pain score at baseline when compared to immediately, at 2 weeks, and at 6 weeks post 3PSI as highlighted below. Conclusion We recommend the injection of prolotherapy using this unique method for pain control in patients with multi-site shoulder pathologies, especially involving ACJ, subacromial structures and GHJ shows great success even until 6 weeks post-procedure.